PENGEMBANGAN ALGORITMA UNTUK PERCEPATAN PROSES KOMPUTASI PARALEL PADA METODE STAGGERED GRID FINITE DIFFERENCE TIME DOMAIN MENGGUNAKAN ARSITEKTUR CUDA GPU - Budiman, Arief; Triono, Joko (JURNAL AGRI-TEK, 2014)
The utilization of parallel computing architecture with cuda gpu has been shown to speed up the computing process time, hence many scientific activities, database application, geometry application, image processing application use parallel architecture to get better computing performances.However computing time speed was also influenced by the proper algorithms, so then in this research will be developed an algorithm program that would be expected to gain more computing speed time process. On this research will be used a method of 2 dimention stagerred grid finite difference time domain.And tools used in this research is c cuda programming language with microsoft visual studio 2007.Kata kunci : GPU, CUDA, 2D Finite Difference Time Domain Stagerred Grid